1994
DOI: 10.1016/s0140-6736(94)91970-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of sentinel headache in aneurysmal subarachnoid haemorrhage

Abstract: Retrospective surveys of patients with subarachnoid haemorrhage suggest that minor episodes with sudden headache (warning leaks) may precede rupture of an aneurysm, and that early recognition and surgery might lead to improved outcome. We studied 148 patients with sudden and severe headache (possible sentinel headache) seen by 252 general practitioners in a 5-year period in the Netherlands. Subarachnoid haemorrhage was the cause in 37 patients (25%) (proven aneurysm in 21, negative angiogram in 6, no angiogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
1
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(174 citation statements)
references
References 24 publications
(15 reference statements)
6
156
1
11
Order By: Relevance
“…[1,4,6] Also some retrospective surveys of patients with subarachnoid haemorrhage suggest that minor episodes with sudden headache (warning leaks) may precede rupture of an aneurysm, and that early recognition and treatment might lead to improved outcome. [7] In different studies the mechanisms underlying TCH due to unruptured aneurysms were diffuse, multifocal and segmental cerebral vasospasm in the absence of haemorrhage, morphologic changes like stretching, expansion, dissection, [8] local thrombosis in the wall [9] and limited leakage of blood which implies that partial rupture has occurred in to the subarachnoid space. [6,10] …”
Section: Pain a Rimentioning
confidence: 99%
“…[1,4,6] Also some retrospective surveys of patients with subarachnoid haemorrhage suggest that minor episodes with sudden headache (warning leaks) may precede rupture of an aneurysm, and that early recognition and treatment might lead to improved outcome. [7] In different studies the mechanisms underlying TCH due to unruptured aneurysms were diffuse, multifocal and segmental cerebral vasospasm in the absence of haemorrhage, morphologic changes like stretching, expansion, dissection, [8] local thrombosis in the wall [9] and limited leakage of blood which implies that partial rupture has occurred in to the subarachnoid space. [6,10] …”
Section: Pain a Rimentioning
confidence: 99%
“…However, this classic description is seen in only 50% of patients presenting with aneurysmal SAH [8]. Conversely, in those patients prospectively screened for acute severe headache, only 6-17% were demonstrated to have SAH [9,10]. Common features at presentation can include seizure, loss of consciousness, and nausea and emesis preceding onset of headache [9].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Conversely, in those patients prospectively screened for acute severe headache, only 6-17% were demonstrated to have SAH [9,10]. Common features at presentation can include seizure, loss of consciousness, and nausea and emesis preceding onset of headache [9]. The concept of 'sentinel headache' remains controversial; it is thought to be related to changes in the wall of the aneurysm versus a microbleed.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…12% (5-18%) of those with headache as the only symptom. 2 Nine studies of good quality, which reported the number of patients with aneurysmal subarachnoid haemorrhage with a history of sentinel headache, gave rates of 10% to 43%, true incidence may vary from near zero to about 40%. 3 Patients with acute vascular disorders of the CNS demonstrate an abundance of both rhythm and morphologic changes in their ECG.…”
Section: Introductionmentioning
confidence: 99%